Pengaruh Teknologi Informasi, Literasi Keuangan Pengguna Dan Kolaborasi Stakeholder Terhadap Implementasi Kartu Kredit Pemerintah Daerah (KKPD) Periode 2022-2024 Di Kabupaten Wonogiri - Okta Ginanjar Astuti; Syahriar Abdullah; Kurniawati, Susilaningtyas Budiana (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to evaluate the implementation of the Regional Government Credit Card (KKPD) in Wonogiri Regency from 2022 to 2024 by analyzing the impact of information technology, financial literacy of users and stakeholder collaboration on the success of KKPD implementation. The background of this study is the government’s effort to improve the efficiency, transparency and accountability of regional financial management through the digitalization of financial transactions with KKPD, despite facing technical and non-technical challenges. The research method used is a quantitative approach with a survey involving officials who are involved in the management of KKPD in the Regional Work Units (OPD) of Wonogiri Regency, with descriptive analysis to describe the results obtained. The results show that information technology, financial literacy of users and stakeholder collaboration play an important role in supporting the success of KKPD implementation, although there are several challenges that need to be addressed to improve the effectiveness of this system.